1990
DOI: 10.1210/jcem-71-6-1675
|View full text |Cite
|
Sign up to set email alerts
|

Women with Preeclampsia have Higher Plasma Endothelin Levels than Women with Normal Pregnancies

Abstract: Endothelin, a newly discovered endothelium-derived peptide, has potent vasoactive properties in vivo and in vitro. The actions of endothelin in clinical conditions of hypertension have not yet been defined. This study examined the possible role of endothelin in the vasospasm and hypertension associated with a well-defined syndrome of gestational hypertension, preeclampsia. Our results indicate that the concentration of immunoreactive endothelin is elevated significantly in plasma obtained from women with preec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
90
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 324 publications
(96 citation statements)
references
References 11 publications
4
90
1
Order By: Relevance
“…Endothelin-1 (ET-1) is a potent vasoconstrictive peptide secreted by endothelial and vascular smooth muscle cells. We 12 and others [13][14][15][16] have shown elevated ET-1 levels in PE. It is possible that endothelial dysfunction induced by the elevated sFLt-1 and sEng levels results in overproduction of ET-1, leading to hypertension and proteinuria.…”
Section: Introductionmentioning
confidence: 59%
“…Endothelin-1 (ET-1) is a potent vasoconstrictive peptide secreted by endothelial and vascular smooth muscle cells. We 12 and others [13][14][15][16] have shown elevated ET-1 levels in PE. It is possible that endothelial dysfunction induced by the elevated sFLt-1 and sEng levels results in overproduction of ET-1, leading to hypertension and proteinuria.…”
Section: Introductionmentioning
confidence: 59%
“…The present results also suggest that the Phe-induced contraction of aortic strips of pregnant rats is enhanced by TNF-␣. On the other hand, preeclampsia is associated with increased plasma levels of endothelin 1 and increased pressor responses to ANG II (40,63). Whether acute treatment with TNF-␣ enhances the vascular contraction to other vasoconstrictors such as endothelin 1 and ANG II and in small resistance vessels with more relevance to preeclampsia is unclear and should represent important areas for future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have reported no significant changes in circulating levels of ET-1 during moderate forms of preeclampsia, a possible role for ET-1 as a paracrine or autocrine agent in preeclampsia remains worthy of consideration. 11,12,23,46,47 Because ET-1 is released toward the vascular smooth muscle in a paracrine fashion, changes in plasma levels of ET may not reflect its local production. Indeed, this is one of the reasons why it has been difficult to ascertain whether preeclampsia is associated with altered ET production.…”
Section: Endothelinmentioning
confidence: 99%